Nation-Building through Civic Education: A Comparative Study of Malaysia and Indonesia - Febri Fajar Pratama; Fazli Rachman; Fajar Nugraha; Hatma Heris Mahendra (Pancasila: Jurnal Keindonesiaan, 2026)
Civic education serves as a key instrument for citizenship formation, although its orientation varies across national contexts. This study comparatively analyses civic education in Malaysia and Indonesia by examining how historical experience, national identity, and socio-cultural contexts shape curriculum orientation and civic values. Using a qualitative literature-based approach, the study analyses academic articles, policy documents, curriculum guidelines, and historical sources from both countries. The findings reveal distinct developmental trajectories. In Malaysia, civic education evolved from Pendidikan Sivik to Pendidikan Sivik dan Kewarganegaraan, emphasising patriotism, ethnic harmony, and social cohesion in response to multicultural pluralism. In contrast, civic education in Indonesia is anchored in Pendidikan Pancasila dan Kewarganegaraan, with Pancasila functioning as the ideological foundation for national identity, democratic values, and citizenship responsibilities. Overall, the study demonstrates that while both countries employ civic education for nation-building, differences in historical experience and ideological orientation lead to divergent curricular emphases and civic outcomes.